2007
DOI: 10.1182/blood-2007-05-087940
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the mechanism of FTY720 and compatibility with regulatory T cells for the inhibition of graft-versus-host disease (GVHD)

Abstract: The immunomodulator FTY720 (FTY) has been shown to be beneficial in experimental models of organ transplantation and autoimmunity. We show that FTY significantly inhibited but did not prevent graftversus-host disease (GVHD) in lethally irradiated or nonirradiated allogeneic recipients. Although most studies implicate prevention of lymphocyte egress from lymphoid organs as the primary mechanism of action, our data indicate that FTY effects on the host are more likely to be responsible for GVHD inhibition. Intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 33 publications
(67 reference statements)
1
74
1
Order By: Relevance
“…If FTY720 was simply preventing lymphocyte egress from SLTs, then one might predict an accumulation of lymphocytes in these tissue sites. Previous work (36) in a model of graft-versus-host disease reported similar findings, which may be related to the effects of FTY720 on DCs' ability to move in the spleen and position themselves for efficient CD4 + T cell activation (35). Our results indicate a similar effect; however, because the drug did not interfere with Ag-specific CD4 + T cell proliferation in the first 3 d of infection (Fig.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…If FTY720 was simply preventing lymphocyte egress from SLTs, then one might predict an accumulation of lymphocytes in these tissue sites. Previous work (36) in a model of graft-versus-host disease reported similar findings, which may be related to the effects of FTY720 on DCs' ability to move in the spleen and position themselves for efficient CD4 + T cell activation (35). Our results indicate a similar effect; however, because the drug did not interfere with Ag-specific CD4 + T cell proliferation in the first 3 d of infection (Fig.…”
Section: Discussioncontrasting
confidence: 40%
“…Data are representative of two independent experiments (n = 4 mice/group). *p , 0.05, **p , 0.01. responder T cells in a model of graft-versus-host disease (36). Therefore, a more detailed analysis of the kinetics of CD4 + T cell responses in the liver and spleen of L. donovani-infected mice treated for 28 d with FTY720 was undertaken (Fig.…”
Section: Donovani-infected Micementioning
confidence: 99%
“…Although it has been suggested that FTY720 may modulate lymphocyte trafficking, especially donor-derived T-cell infiltration into target organs, to inhibit aGVHD, 20,39,40 another recent study demonstrated that FTY720 did not inhibit donor effector T-cell trafficking into the aGVHD target organs. 41 The same report also showed FTY720 reduced the number of DCs in the target organs, which has been suggested to be the mechanism underlying aGVHD inhibition. We did not observe any changes in DCs in the GVHD target organs with CYM treatment.…”
Section: Discussionmentioning
confidence: 75%
“…23 Lethally irradiated Balb/c recipients undergoing BMT received A20 luc (10 5 ). Groups received 2 ϫ 10 6 CD25 Ϫ Teffs from wild type (wt), IL-21 Ϫ/Ϫ , IL-21R Ϫ/Ϫ , or perforin Ϫ/Ϫ mice in the presence or absence of anti-IL-21 mAb, as indicated, for a period of 6 weeks.…”
Section: Assessment Of Gvl Activitymentioning
confidence: 99%